2004
DOI: 10.1021/bi048385b
|View full text |Cite
|
Sign up to set email alerts
|

Direct Evidence That the Reaction Intermediate of Metallo-β-lactamase L1 Is Metal Bound

Abstract: In an effort to probe the structure of the reaction intermediate of metallo-beta-lactamase L1 when reacted with nitrocefin and other beta-lactams, time-dependent absorption and rapid-freeze-quench (RFQ) EPR spectra were obtained using the Co(II)-substituted form of the enzyme. When using nitrocefin as the substrate, time-dependent absorption spectra demonstrate that Co(II)-substituted L1 utilizes a reaction mechanism, similar to that of the native Zn(II) enzyme, in which a short-lived intermediate forms. RFQ-E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
127
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(146 citation statements)
references
References 62 publications
18
127
0
1
Order By: Relevance
“…It is important to note that the recent computational study suggested that a tetrahedral intermediate does not form in the proposed mechanism of CphA (52), and our data cannot support nor refute this hypothesis. It is entirely possible that EI is in fact a ring-opened, unprotonated species, similar to that reported in studies with CcrA and L1 when reacted with nitrocefin (17,19,21). In either case, a proton must be transferred to the ring-opened, nitrogen to generate product.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…It is important to note that the recent computational study suggested that a tetrahedral intermediate does not form in the proposed mechanism of CphA (52), and our data cannot support nor refute this hypothesis. It is entirely possible that EI is in fact a ring-opened, unprotonated species, similar to that reported in studies with CcrA and L1 when reacted with nitrocefin (17,19,21). In either case, a proton must be transferred to the ring-opened, nitrogen to generate product.…”
Section: Discussionsupporting
confidence: 56%
“…The product signal was isolated ( Figure 7F) by subtraction of the resting signal from Figure 6I and could be simulated ( Figure 7G) assuming S = 3/2, M S = |± 1/2〉, g x,y = 2.35, g z = 2.12, E/D = 0.13. An enzyme bound product signal was also observed in RFQ EPR spectra of B3 metallo-β-lactamase L1 (21).…”
Section: Rapid Freeze Quench Epr Studiesmentioning
confidence: 75%
“…In canonical metallo-β-lactamases, the hydroxide that bridges the two zinc ions is the nucleophile for the hydrolysis reaction, and the substrate is directly liganded to the zinc atoms 23 . In our structure, the hydroxide is placed directly below the sulfate group (Fig.…”
mentioning
confidence: 99%
“…Considerable information exists regarding the B1 and B3 enzymes, including X-ray diffraction (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29), spectroscopic (9,(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42), mechanistic (43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59), and computational studies (60)(61)(62)(63)(64)…”
mentioning
confidence: 99%